COMPARATIVE ASSESSMENT OF LARGE ARTERY ELASTICITY IN PATIENTS WITH STABLE ANGINA RECEIVING METABOLIC THERAPY - O. V. Ilukhin; D. L. Tarasov; A. K. Prom; E. L. Kalganova; T. Kh. Termisultanova; M. V. Ilukhina (Российский кардиологический журнал)
Aim. To assess the effects of metabolic therapy, administered together with standard antianginal treatment, on large artery elasticity and endotheliumdependent vasodilation in patients with stable angina and subsequent heart failure. Material and methods. The study included 74 patients with coronary heart disease (CHD), stable angina of II–III Functional Class (FC), and FC II–III chronic heart failure (CHF). In the main group, standard antianginal treatment was combined with metabolic therapy (trimetazidine, trimethylhydrazinium propionate, and isosorbide dinitrate) for 4 months; the control group received standard treatment only. Results. The four-month metabolic therapy failed to substantially improve the pulse wave velocity (PWV) in elastic arteries. In muscular arteries, PWV significantly decreased during the treatment with isosorbide dinitrate, which negatively affected endothelium-dependent vasodilation of radial arteries. However, trimetazidine treatment was associated with a significant improvement in endothelial function, as well as with a significant reduction in anginal FC and a substantial improvement in exercise capacity. Trimethylhydrazinium propionate therapy was linked to non-significant positive dynamics of these parameters. Conclusion. In stable angina patients, the combination of trimetazidine and standard antianginal therapy was associated with a significant improvement in endotheliumdependentvasodilation of muscular arteries. Consideringits positiveimpact on endothelial function and the absence of direct effects on arterial tonus in stable angina, trimetazidine therapy was more effective than isosorbide dinitrate treatment.